Quantitative analysis of cell walls of nutritionally variant streptococci grown under various growth conditions. - van de Rijn, I (1985)
Strains of nutritionally variant streptococci are usually isolated from patients with subacute bacterial endocarditis. Only recently have these strains been subdivided into three serotypes; however, no group-specific antigen has been described. To understand the immunochemical basis for the serology of these microorganisms as well as set the groundwork for adherence studies, quantitative analysis of the cell walls of nutritionally variant streptococci was undertaken. The bacteria were grown in semisynthetic medium or pyridoxal-supplemented Todd-Hewitt broth and harvested during the exponential or stationary phase. Cell walls were isolated and analyzed for amino sugars, sugars, polyalcohols, amino acids, and phosphorus by gas chromatography, high-pressure liquid chromatography, or colorimetric assays. The peptidoglycans of the cell walls of the prototype strains from the three serotypes were representative of other streptococcal cell walls, including the presence of alanine as the possible cross-bridge. The composition of the peptidoglycan was similar for all three strains and included a decreased concentration of peptidoglycan in their cell walls during the stationary phase. Glucosamine, glucose, galactose, ribitol, and a small amount of rhamnose were found in each of the cell wall polysaccharides. Galactosamine was only found in serotype II and III cell walls and might be responsible for the previously described cross-reaction between these strains. The concentration of the other sugars and amino sugars varied in each of the cell wall preparations, depending on the growth conditions. Finally, all three strains expressed both ribitol and phosphorus in their cell walls, characteristic of the presence of a ribitol teichoic acid. Therefore the cell wall composition of the nutritionally variant streptococci varies depending on the growth conditions, and their composition appears similar to that of strains of Streptococcus mitis.